2006
DOI: 10.1152/ajpendo.00436.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-dependent expansion of pancreatic β-cells by the protein p8 in vitro and in vivo

Abstract: . Glucose-dependent expansion of pancreatic ␤-cells by the protein p8 in vitro and in vivo. Am J Physiol Endocrinol Metab 291: E1168 -E1176, 2006. First published July 18, 2006 doi:10.1152/ajpendo.00436.2005.-p8 protein expression is known to be upregulated in the exocrine pancreas during acute pancreatitis. Own previous work revealed glucose-dependent p8 expression also in endocrine pancreatic ␤-cells. Here we demonstrate that glucose-induced INS-1 ␤-cell expansion is preceded by p8 protein expression. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…p8 either stimulates (Päth et al, 2006) or inhibits (Jiang et al, 2006) cell growth, the outcome depending on association with other transcription factors (Jiang et al, 2005). Moreover, p8 promotes (Carracedo et al, apoptosis, the latter via interaction with prothymosin a .…”
Section: Discussionmentioning
confidence: 99%
“…p8 either stimulates (Päth et al, 2006) or inhibits (Jiang et al, 2006) cell growth, the outcome depending on association with other transcription factors (Jiang et al, 2005). Moreover, p8 promotes (Carracedo et al, apoptosis, the latter via interaction with prothymosin a .…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this idea, pancreatic ß-cell expansion is induced by glucose-stimulated proliferation [29][32], and glucose-mediated reduction of apoptosis [33], [34]. However, glucotoxicity has been linked to persistent hyperglycemia in type II diabetes as a result of impaired ß-cell proliferation [35], [36] and increased apoptosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that fibroblasts isolated from p8 -/- mice showed increased cell proliferation [ 34 ], and silencing of p8 in pancreatic cell lines also results in the latter [ 35 ]. In contrast, p8 overexpression is accompanied by upregulated proliferation of beta cells; however, this was only observed in the presence of glucose [ 19 ]. Additionally, p8 overexpression results in reduced beta-cell-related gene expression, insulin content and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α) lead to upregulation of p8 [ 9 ], and glucose-dependent stimulation of p8 was observed in INS-1 insulinoma cells [ 18 ]. Overexpression of p8 in human islets leads to augmented insulin secretion, as well as cellular insulin content and improved glycemic control [ 19 ]. In contrast, p8 −/− mice show mild insulin resistance compared to wild type animals but maintained normoglycemia through increase of beta cell mass and consecutive hyperinsulinemia [ 20 ].…”
Section: Introductionmentioning
confidence: 99%